2012
DOI: 10.1159/000341340
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Troponin T in Patients with Acute Ischemic Stroke

Abstract: Background: Newly developed troponin assays have superior diagnostic and prognostic performance in acute coronary syndrome (ACS), when compared to conventional troponin assays; however, highly sensitive troponin has not been evaluated in patients with acute ischemic stroke. Methods: Highly sensitive troponin T (hsTnT) was measured daily during the first 4 days in 193 consecutive patients with acute ischemic stroke without overt ACS or atrial fibrillation. The patients were previously tested normal with a fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 62 publications
2
26
0
1
Order By: Relevance
“…Recently higher Troponin T levels were found in older patients with a more severe ischemic stroke and with comorbidities such as heart failure and/or renal insufficiency [39]. Another study showed that elevated levels of high sensitive Troponin T are frequently present in patients with acute ischemic stroke but, in accordance to our results, did not provide additional prognostic information in these subjects [40]. Interestingly s-cTnI did also not provide additional information for the identification of cardioembolic aetiology in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Recently higher Troponin T levels were found in older patients with a more severe ischemic stroke and with comorbidities such as heart failure and/or renal insufficiency [39]. Another study showed that elevated levels of high sensitive Troponin T are frequently present in patients with acute ischemic stroke but, in accordance to our results, did not provide additional prognostic information in these subjects [40]. Interestingly s-cTnI did also not provide additional information for the identification of cardioembolic aetiology in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Despite the great interest in soluble ST2, GDF-15 and hsTn in coronary heart disease, 23,24 heart failure, 25-28 and ischemic stroke, 29,30 and in the general population where concentrations of each have been shown to predict future heart failure, coronary heart disease, and mortality, 8,31-33 only sparse data are available relating these biomarkers to risk of incident AF. To date, contradictory results have been published regarding the value of elevated TnI levels to predict AF in the post-operative setting after coronary artery bypass graft surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sensitivity of troponin assays has continued to improve over time, such that the group of troponin-positive patients has become larger and more diverse over time [21,22] . One analysis by Jensen et al [13] found that one-third of stroke patients who tested negative for troponin would be considered troponin-positive when a highly-sensitive assay was used several years later. Despite these differences, a systematic review of 15 studies including 2,901 patients with ischemic stroke found that 18% of these individuals had an elevated troponin level during the stroke hospitalization [11] , a number remarkably similar to the 17% of patients with abnormal troponin values in our study.…”
Section: Prior Troponin Studiesmentioning
confidence: 99%
“…Despite relatively consistent literature suggesting a relationship between troponin elevation and mortality [8][9][10][11][12] , some authors have suggested that risk was related to patient age, stroke severity, electrocardiographic changes, and the presence of comorbid conditions [13] . These analyses were generally based on smaller, frequently European cohorts with more homogeneous patient populations and variable clinical management protocols [8-15, 17, 20-23] .…”
Section: Prior Troponin Studiesmentioning
confidence: 99%